Salingers depiction of trauma in The Catcher in the Rye - Wan Yahya, Wan Roselezam; Babaee, Ruzbeh (Academy Publication Co., Ltd, 2014)
Although J. D. Salinger’s The Catcher in the Rye (1951) is one of the most widely read novels in American literature, it has usually been prohibited in academic centers across the US from its publication.While many things were taboo and banned in 1950s America, Salinger talks about them frankly through his novel. From the time of its first publication, The Catcher has been seen as a depiction of trauma for many adolescents and young readers who have observed themselves opposed to the values of America. Salinger pursues a style of romantic individualism and sees society as innately corrupt.As a “trauma fiction,” The Catcherexhibits the author’s tormented relation to the war.The present study exploresthe root of trauma through the protagonist of the novel.